THE MEANING OF ASSETS BASED ON LOCAL WISDOM AND RELIGIOSITY: A TRANSCENDENTAL PHENOMENOLOGICAL STUDY - Mohamad Anwar Thalib (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2025)
This study explores the meaning of assets based on local cultural values and religiosity among university students in Gorontalo. Using an interpretive paradigm with a transcendental phenomenological approach, data were collected through in-depth interviews with selected informants and analyzed using five stages: noema, epoche, noesis, intentional analysis, and eidetic reduction. The findings reveal that assets are not only perceived as material possessions but also encompass social, spiritual, and cultural dimensions. Assets are understood as wealth that benefits others, a medium to help the community, faith in Allah SWT as the most valuable treasure, and the human body and dignity as divine trust. These meanings highlight a broader perspective of assets compared to modern accounting, which tends to emphasize material aspects. Theoretical implications of this research lie in expanding the conceptual framework of accounting by integrating social, cultural, and religious dimensions into the understanding of assets, thereby contributing to the development of a more holistic and humanistic accounting discourse. Practical implications show that non-material assets such as faith, solidarity, and dignity can serve as the basis for decision-making in personal finance, social participation, and organizational practices. This study emphasizes that accounting should not be limited to economic gain but also oriented toward social usefulness, cultural preservation, and spiritual accountability.